Unconstitutional aspects of Peruvian family law - Reyes Castillo, Eduardo Antonio (2025)
This paper aimed to address seven institutions within Peruvian family law that require analysis in terms of their constitutionality and continued existence within the Peruvian legal system, particularly in civil law. The main findings of this research identified inequality in the adoption of the spouse’s surname, equal rights of parents in the registration of their children, regulation of same-sex families, protection of privacy in no-fault divorces, the identity of the child receiving alimony, freedom of property regimes in de facto unions, and equal protection of cohabiting partners in matters of disinheritance and indignity. The methodology was qualitative-descriptive, using documentary analysis, and concluded that these legal institutions violate fundamental rights due to lack of regulation, persistence without reform, or inconsistency with the principles of family law.